Sterilization of Drug-Loaded Composite Coatings for Implantable Glucose Biosensors. (May 2021) - Tipnis, Namita; Kastellorizios, Michail; Legassey, Allen; Papadimitrakopoulos, Fotios; Jain, Faquir; Burgess, Diane J.
Background: An anti-inflammatory drug-loaded composite coating (dexamethasone-loaded poly (lactic-co-glycolic acid) [PLGA] microspheres/polyvinyl alcohol [PVA] hydrogel) was previously developed to counter the foreign body reaction to a fully implantable continuous glucose monitoring biosensor. The long-term sensor functionality was ensured in the presence of the drug-loaded composite coating thus facilitating better diabetes control and management. In order to advance such a drug-device combination product toward clinical testing, addressing sterilization remains a key step due to the heterogeneity of the product components. The main objective of this research was to investigate the effect of two terminal sterilization techniques: gamma radiation and ethylene oxide (EO) on the stability of the anti-inflammatory coatings as well as retention of the glucose sensing ability of the implantable sensor. Method: The composite coatings, their individual components, and the glucose-sensing elements of the biosensor were subjected to low-temperature gamma radiation and EO cycles. Detailed characterization was conducted on all components before and after sterilization. Results: Exposure to gamma radiation affected dexamethasone crystallinity and glucose response linearity of the sensing element, whereas physical aging of microspheres in composite coatings was observed poststerilization with EO. Despite these effects, dexamethasone drug release from coatings was not significantly affected by either technique. Conclusion: The research findings indicate that both sterilization techniques are feasible for the sterilization of the dexamethasone-loaded PLGA microspheres/PVA hydrogel composite coatings, while EO was preferred for the sterilization of the glucose-sensing element of the biosensor.